The roles of polyamines in Malaysian herbs as a chemoprevention strategy: a scoping review - Azalan, Maryam Syahidah; Abdul Ghani, Radiah; Wallace, Heather M. (Universiti Putra Malaysia, 2023)
Maintaining normal polyamine levels is crucial for the physiological cellular process and differentiation because an imbalance of polyamine concentration affects the occurrence of neoplastic activities in many types of cancer diseases. Malaysian herbs have been purported to have anticancer properties that influence the polyamine’s bioavailability, leading to cancer cell death. Presently, the roles of polyamines in Malaysian herbs as chemoprevention have yet to be documented. Thus, this review aims to determine which Malaysian herbs have chemoprevention properties affecting polyamines and appraise the relationship between polyamine levels and Malaysian herbs and their cytotoxicity on cancer cells. The search, employing keywords like “Malaysian herbs”, “polyamines”, and “anticancer” or “chemoprevention”, yielded 256 articles. The articles were screened for their eligibility, befitting the objectives mentioned. The PRISMA-ScR checklist was employed to report the published findings from the databases. Thirteen articles meeting inclusion criteria were selected, highlighting 13 Malaysian herbs influencing the intracellular polyamines pathway. All herbs showed a significant reduction in ornithine decarboxylase (ODC) expression. In addition, Alpinia galanga and Aloe barbadensis showed an increase in catabolic polyamines expression, spermidine/spermine-N-acetyl transferase (SSAT) and spermine oxidase (SMO), respectively, leading to growth arrest and induction of apoptosis in cancer cells. The in vitro and in vivo studies demonstrated these herbs’ anti-proliferative effects on diverse cancer types, involving polyamine level modulation, intracellular dynamics, and chemopreventive mechanisms through apoptosis and anti-inflammatory responses. The findings underscore the potential of Malaysian herbs in cancer prevention by modulating the polyamine pathway.